Brows Asymmetry Correction With the Direct Approach: Myth or Reality?. Issue 2 (March 2016) - Pascali, Michele; Carinci, Francesco; Bocchini, Ilaria; Avantaggiato, Anna; Cervelli, Valerio
Abstract : Objectives: The current article is aimed to test the effectiveness of direct and indirect brow lifting to correct brows asymmetry. Methods: Fifty patients treated with direct brow lift between January of 2011 and January of 2013 were investigated. All patients were men and treated under local anesthesia. In all patients, the brow lifting was associated with an upper blepharoplasty. The amount of brow elevation produced was assessed by comparison of the preoperative and at 1-year postoperative vertical distances between the superior eyebrow hairline and the interpupillary line at midpupil and at lateral and medial canthus. Paired sample t -test was used to investigate brow lifting amelioration after 1 year. The differences in measurements between the 2 sides were plotted to evaluate the degree of symmetry between 2 sides. In addition, a comparison was performed; a series of 45 patients treated with temporal (ie, indirect) approach. Results and Conclusions: The paired sample test demonstrated that direct brow lifting is a proper surgical technique to correct brow asymmetry. Also temporal (ie, indirect) approach is able to ameliorate brow asymmetry but direct technique provide better results. The direct brow lifting is a reliable, reproducible and safe surgical procedure, provides excellent and long-lasting results, and is very efficacious in brows asymmetry correction.